Implementation of Government Regulation Number 7 of 2021 Concerning The Facilitation, Protection, and Empowerment of Cooperatives and Micro, Small, and Medium Enterprises: (Entrepreneurship Training "Sekabu Cent: Utilization Of Rice Husks And Bagasse Into Bakhoor") - Ade Wahyuni Azhar; Melvi Fitri; Ali Umar (Journal of Community Service and Engagement, 2026)
The implementation of Government Regulation Number 7 of 2021 concerning the Facilitation, Protection, and Empowerment of Cooperatives and Micro, Small, and Medium Enterprises (MSMEs) emphasizes the importance of strengthening community-based entrepreneurship through innovation and the utilization of local resources. One of the strategic efforts to support this objective is the entrepreneurship training program entitled “SEKABU CENT: Utilization of Rice Husks and Bagasse into Bakhoor.” This program aims to enhance entrepreneurial capacity, improve environmental awareness, and create value-added products from agricultural waste materials that are often underutilized. The training targeted community members and prospective entrepreneurs by providing knowledge and practical skills in processing rice husks and sugarcane bagasse into bakhoor products with economic value. The method employed included socialization activities, hands-on workshops, mentoring sessions, and product development practices. The results indicate that participants gained a better understanding of waste utilization, entrepreneurial management, and product marketing strategies. Participants were also able to produce innovative bakhoor products with potential market competitiveness while contributing to environmental sustainability through waste reduction. The program demonstrates that entrepreneurship training based on local resource utilization can serve as an effective instrument for implementing Government Regulation Number 7 of 2021 by fostering economic empowerment, encouraging business independence, and supporting the growth of sustainable MSMEs. These findings highlight the significance of integrating entrepreneurship education with local potential development to strengthen community economic resilience and promote inclusive economic growth.